Half of the World in Light : New and Selected Poems - Herrera, Juan Felipe (Book collections on Project MUSE., 2008)
"For nearly four decades, Juan Felipe Herrera has documented his experience as a Chicano in the United States and Latin America through stunning, memorable poetry that is both personal and universal in its impact, themes, and approach. Often political, never fainthearted, his career has been marked by tremendous virtuosity and a unique sensibility for uncovering the unknown and the unexpected. Through a variety of stages and transformations, Herrera has evolved more than almost any other Chicano poet, always re-inventing himself into a more mature and seasoned voice. Now, in this unprecedented collection, we encounter the trajectory of this highly innovative and original writer, bringing the full scope of his singular vision into view. Beginning with early material from A Certain Man and moving through thirteen of his collections into new, previously unpublished work, this assemblage also includes an audio CD of the author reading twenty-four selected poems aloud. Serious scholars and readers alike will now have available to them a representative set of glimpses into his production as well as his origins and personal development. The ultimate value of bringing together such a collection, however, is that it will allow us to better understand and appreciate the complexity of what this major American poet is all about."--Publisher's description.